The Panama Papers proved encryption is a massive asset for democracy - Obermaya, Bastian (euronews, 2023)
We should celebrate the transformative power of encryption and spotlight the incredible things it has done in the fight to expose injustice and give a voice to the voiceless.
Keywords: 2023-10 October